ANALISIS LITERASI DIGITAL CALON GURU KIMIA DALAM PELAKSANAAN PPL BERBASIS VIRTUAL DI MASA PANDEMI COVID-19 - Wiwik Kartika Sari; Ella Izzatin Nada (Orbital: Jurnal Pendidikan Kimia, 2020)
The COVID-19 pandemic has changed the offline learning process to be online, including the implementation of Field Experience Practices (PPL) activities carried out by chemistry education students. The online learning process which is carried out requires students to be proficient in the use of technology. This study aims to analyze the digital literacy skills of chemistry teacher candidate students. This research is a qualitative descriptive which the subjects were 60 students of chemistry education. Data were collected through survey and interview techniques. The instrument used to collect data was a digital literacy questionnaire which was declared valid and reliable based on the instrument test results. The digital literacy aspects tested are information, communication, content creation, safety, and problem solving. Based on the research data analysis, it can be concluded that the digital literacy skills of chemistry teacher candidate students are good. The percentage of the digital literacy level of chemistry education students on each indicator was 87% in the information category, 82% in the communication category, 78% in the content-creator category, 82% in the safety category, and 82% in the problem solving category.